The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/acm2.12415
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis using machine learning to predict for chest wall pain in patients with stage I non‐small‐cell lung cancer treated with stereotactic body radiation therapy

Abstract: Background and purposeChest wall toxicity is observed after stereotactic body radiation therapy (SBRT) for peripherally located lung tumors. We utilize machine learning algorithms to identify toxicity predictors to develop dose–volume constraints.Materials and methodsTwenty‐five patient, tumor, and dosimetric features were recorded for 197 consecutive patients with Stage I NSCLC treated with SBRT, 11 of whom (5.6%) developed CTCAEv4 grade ≥2 chest wall pain. Decision tree modeling was used to determine chest w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Given the result from our machine learning analysis that none of the 35 features analyzed performed better than a random classifier, this suggests that our currently utilized clinical, demographic, and dosimetric features could be inadequate to reliably predict radiation esophagitis. One can conclude that we are not currently collecting and capturing the appropriate features to allow a machine learning workflow to predict grade 3 radiation esophagitis, as we were successfully able to do when using machine learning to predict for pneumonitis in LA-NSCLC [41] and chest wall toxicity in early stage NSCLC [42]. As such, we encourage other investigators to explore and develop new markers directed at this toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…Given the result from our machine learning analysis that none of the 35 features analyzed performed better than a random classifier, this suggests that our currently utilized clinical, demographic, and dosimetric features could be inadequate to reliably predict radiation esophagitis. One can conclude that we are not currently collecting and capturing the appropriate features to allow a machine learning workflow to predict grade 3 radiation esophagitis, as we were successfully able to do when using machine learning to predict for pneumonitis in LA-NSCLC [41] and chest wall toxicity in early stage NSCLC [42]. As such, we encourage other investigators to explore and develop new markers directed at this toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, there is a tremendous increase in the use of ML in different areas of radiation oncology, such as treatment planning optimization, segmentation, radiation physics quality assurance, contouring or image‐guided radiotherapy . In this paper, we focus on ML for radiation outcome modeling …”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer RT may cause chest pain due to rib fracture, radiation-induced neuropathy of the intercostal nerves or nerve branches, chest wall edema, or chest wall fibrosis. However, the only study we found that specifically investigated chest pain is the one by (34). The authors utilized decision tree and RF methods to identify robust features predictive of chest wall pain in a cohort of 197 patients.…”
Section: Lungmentioning
confidence: 99%